Exploring tourism attractiveness factors and consumption patterns of Southeast Asian tourists to Taiwan - Wei-Tse Pai; Jie-Min Lee; Ji-Feng Ding; Ca-Van Pham (Cogent Social Sciences)
In an attempt to drive tourist interest, Taiwan implemented a series of changes in 2016 seeking to attract new and repeat visitors. Using a sample of 2339 international tourists visiting Taiwan from 2017 to 2020, we aimed to analyze the attractiveness factors of Southeast Asian tourists to Taiwan and their impact on tourism consumption demand. Employing the Almost Ideal Demand System model by Deaton and Muellbauer (1980), our findings indicate that specialty food, natural scenery, and shopping are the main attractive factors for Southeast Asian tourists to Taiwan. This study’s theoretical contribution is significant, as it demonstrates the direct or indirect influence of tourist attractiveness factors on the pattern of tourism consumption expenditure. Moreover, the findings have practical implications, suggesting considerable variation in Southeast Asian tourists’ tourism consumption demands and price elasticity across different countries.